PENGARUH DEBT TO EQUITY RATIO, RETURN ON ASSETS (ROA) DAN RETURN ON EQUITY (ROE) TERHADAP HARGA SAHAM PADA PT ASTRA INTERNATIONAL - Ida Yusnita (Indonesian Journal of Thousand Literacies, 2023)
The purpose of this study was to determine how the influence of Debt To Equity Ratio (DER), Return On Assets (ROA) and Return On Equity (ROE) Against Stock Prices At PT Astra International Tbk. 2009-2018. The object of this research is PT Astra International Tbk. obtained from idx.co.id with data for ten years from 2009 to 2018. Data analysis techniques used are multiple linear regression, coefficient of determination, t test and F test. The results of the study indicate that the Debt to Equity Ratio (DER) insignificant effect on Share Prices at PT Astra International Tbk. In 2009-2018, this was proven by t arithmetic <t table (1.354 <2.44691). Return On Assets (ROA) has a significant effect on stock prices at PT Astra International Tbk. In 2009-2018, this was proven by t arithmetic> t table (4,040> 2,44691). Return On Equity (ROE) has no significant effect on stock prices at PT Astra International Tbk. In 2009-2018, this was proven by t count <t table (- 4.068 <2.44691). Simultaneously Debt To Equity Ratio (DER), Return On Assets (ROA) and Return On Equity (ROE) have a significant effect on stock prices at PT Astra International Tbk. The year 2009-2018 is proven by Fcount> Ftable or 7.069> 4.76. The magnitude of the influence of Debt To Equity Ratio (DER), Return On Assets (ROA) and Return On Equity (ROE) on Share Prices at PT Astra International Tbk. In 2009-2018 it was 77.9%. While the remaining 22.1% is influenced by other factors not examined in this study